Gestational age and neonatal brain microstructure in term born infants: a birth cohort study. - Birit F P Broekman; Changqing Wang; Yue Li; Anne Rifkin-Graboi; Seang Mei Saw; Yap-Seng Chong; Kenneth Kwek; Peter D Gluckman; Marielle V Fortier; Michael J Meaney; Anqi Qiu; GUSTO Study Group (PLoS ONE)
Objective Understanding healthy brain development in utero is crucial in order to detect abnormal developmental trajectories due to developmental disorders. However, in most studies neuroimaging was done after a significant postnatal period, and in those studies that performed neuroimaging on fetuses, the quality of data has been affected due to complications of scanning during pregnancy. To understand healthy brain development between 37-41 weeks of gestational age, our study assessed the in utero growth of the brain in healthy term born babies with DTI scanning soon after birth. Methods A cohort of 93 infants recruited from maternity hospitals in Singapore underwent diffusion tensor imaging between 5 to 17 days after birth. We did a cross-sectional examination of white matter microstructure of the brain among healthy term infants as a function of gestational age via voxel-based analysis on fractional anisotropy. Results Greater gestational age at birth in term infants was associated with larger fractional anisotropy values in early developing brain regions, when corrected for age at scan. Specifically, it was associated with a cluster located at the corpus callosum (corrected p<0.001), as well as another cluster spanning areas of the anterior corona radiata, anterior limb of internal capsule, and external capsule (corrected p<0.001). Conclusions Our findings show variation in brain maturation associated with gestational age amongst 'term' infants, with increased brain maturation when born with a relatively higher gestational age in comparison to those infants born with a relatively younger gestational age. Future studies should explore if these differences in brain maturation between 37 and 41 weeks of gestational age will persist over time due to development outside the womb.